A disastrous complication of colonephrocutaneous fistula: brain abscess - Kodiron, Muhammad Afiq; Kamarulzaman, Mohd Nazli; Awang, Mohamed Saufi; Haroon, Raihanah (2021)
A rare case of colonephrocutaneous fistula complicated with a brain abscess is a lifethreatening clinical condition. We report a case of a 35-year-old lady with a history of partial left nephrectomy complicated with left colonic injury who presented with persistent vomiting associated with headache and blurry vision for 5 days. Clinically, she was confused and restless with Glasgow Coma Scale (GCS) of 12/15, however her pupils were equal and reactive bilaterally. Other neurological examinations were unremarkable. Abdominal examination noted functioning ileostomy with a skin opening at left lumbar with pus discharge. Diagnosis of brain abscess was made after contrasted computed tomography (CT) scan of brain. Urgent open drainage surgery was done followed by long course of antibiotic. Contrasted CT abdomen and fistulogram revealed a left colo-psoas and left nephrocutaneous fistula, hence, she was subjected for surgery. Intraoperatively, there was a fistula tract connecting the descending colon, remaining of left kidney, and the skin. Thus, left hemicolectomy, completion of left nephrectomy, and fistulectomy was done. The long-standing infective foci can lead to septic emboli and causes formation of abscess at distant site. Its management is challenging involving both medical and surgical therapy.